Segregation of selected agronomic traits in six S1 cassava families - Kawuki, Robert S.; Nuwamanya, E.; Labuschagne, Maryke T.; Herselman, L.; Ferguson, Morag E. (2011)
Inbreeding of predominantly cross-pollinating crops is expected to result in the generation of progeny with reduced fitness and/or progeny with improved phenotypes. However, this effect is not well documented in cassava (Manihot esculenta Crantz). In this study, S1 progeny from six cassava genotypes (I92/00067, TMS 30572, 95/SE-00036, NASE 4, MH95/0469 and Bamunanika) were examined for five traits: fresh root yield (FRY), fresh foliage yield (FFY), harvest index (HI), root dry matter content (DMC) and amylose content in order to study the effects of inbreeding on these traits. Considerable variations were observed among S1 progeny for FRY (0.0 - 4.3 kg plant-1); FFY (0.2 to 10.2 kg plant-1); HI (0.00 - 0.69); DMC (11.0 - 42%) and amylose content (11.8 to 34.2%). Moreover, in each trait, individual S1 clones existed that substantially outperformed the non-inbred parents. This was particularly true for amylose content where individual S1 clones in each family had higher amylose content than their respective non-inbred parent. Nevertheless, with introduction of inbreeding an average reduction of 61, 33.8, 24.6 and 13.2% was observed for FRY, HI, FFY and DMC. These results demonstrate that with introduction of inbreeding in cassava, it is possible to generate improved phenotypes, which should be the focus of breeders.